Ambidextrous leadership and financial performance of Indonesian microfinance institutions: The role of business model and environmental dynamism - Syahrul Effendi; Idris Gautama So; Nugroho Juli Setiadi; Gatot Soepriyanto (Problems and Perspectives in Management, 2024)
This study aims to investigate the relationship between ambidextrous leadership, business models, and financial performance of Indonesia’s microfinance institutions (MFIs) while also exploring the mediating role of business models and the moderating effect of environmental dynamism in this relationship. Data were collected from 104 microfinance institutions in Indonesia and analyzed using the mediation moderation procedure (ModMed) with macro Process 4.0. The results indicate a positive relationship between ambidextrous leadership, business model, and financial performance. As expected, the study also reveals that the MFI business model is positively related to financial performance and mediates the relationship between ambidextrous leadership and financial performance. The moderating analysis has confirmed the role of environmental dynamism in the relationship between business models and financial performance. The findings provide valuable insights for practitioners in the microfinance sector, suggesting that fostering ambidextrous leadership can enhance the effectiveness of business models, ultimately leading to improved financial performance. Moreover, this paper contributes to the existing literature by examining complex models on the relationship between ambidextrous leadership and financial performance by integrating business models and environmental dynamism within Indonesia’s microfinance institutions. AcknowledgmentBeasiswa Pendidikan Indonesia (BPI) supported this paper and its publication. We thank Lembaga Pengelola Dana Pendidikan (LPDP) and Balai Pembiayaan Pendidikan Tinggi (BPPT) Pusat Layanan Pembiayaan Pendidikan (PUSLAPDIK) for funding this article with grant number 03426/BPPT/BPI.06/9/2023.